2014
DOI: 10.1007/978-3-319-10978-7_9
|View full text |Cite
|
Sign up to set email alerts
|

A Configurable, Inexpensive, Portable, Multi-channel, Multi-frequency, Multi-chromatic RGB LED System for SSVEP Stimulation

Abstract: Steady state visual evoked potential (SSVEP) is extensively used in the research of brain-computer interface (BCI) and require a controllable and configurable light source. SSVEP requires appropriate control of visual stimulus parameters, such as flicker frequency, light intensity, multi-frequency light source and multi-spectral compositions. Light emitting diodes (LEDs) are extensively used as a light source as they are energy efficient, low power, multi-chromatic, have higher contrast, and support wider freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Studies have used light-emitting diode (LED)-based visual stimulus designs that can produce visual flickers without any frequency restrictions and can also produce multiple visual stimuli using the same control platform [22,23]. When using multiple visual stimuli flashing at different frequencies, the accuracy of the flicker frequency for visual stimulus plays an important role in SSVEP-based BCI.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have used light-emitting diode (LED)-based visual stimulus designs that can produce visual flickers without any frequency restrictions and can also produce multiple visual stimuli using the same control platform [22,23]. When using multiple visual stimuli flashing at different frequencies, the accuracy of the flicker frequency for visual stimulus plays an important role in SSVEP-based BCI.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of the HiFiBerry has broadened the range of studies that can be performed using a Raspberry Pi. Previous work from Kuziek et al (2017) and Mouli et al (2015) showed that open source stimulation systems could be used to present simple stimulation (beeps). Our solution extends their work by allowing all types of (personalized) audio protocols with good sound quality.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of a Raspberry Pi use in multisite neuroscientific studies results from multisensory studies on rodent behavior ( Buscher et al, 2020 ). Others have shown that an Arduino could be easily used for steady-state visual evoked potential ( Mouli et al, 2015 ). However, these systems have been developed for very simple protocols and materials (beeps) and could be improved both in timing accuracy and audio quality.…”
Section: Introductionmentioning
confidence: 99%
“…Distance is set approximately one meter. Based on the studies in [5]- [7] found that the optimal parameter for the subject to reduce visual fatigue or visual discomfort. For each trial, therefore, we set the duty cycle (D) is 0.7, flickering rate (F) is fixed at 7 Hz, light intensity (I) is 10%, and chromatic color (C) is green.…”
Section: Methodsmentioning
confidence: 99%